OP0047 GENOME-WIDE ASSOCIATION STUDY OF SJÖGREN'S SYNDROME IDENTIFIES TEN NEW RISK LOCI. (2nd June 2020) - Khatri, B.; Reksten, T. R.; Tessneer, K. L.; Rasmussen, A.; Scofield, R. H.; Bowman, S. J.; Guthridge, J.; James, J. A.; Ronnblom, L.; Warner, B. M.; Mariette, X.; Omdal, R.; et al.
Abstract : Background: Sjögren's syndrome (SS) is a complex autoimmune disease with exocrine gland dysfunction leading to substantial morbidity. There are 10 published genetic susceptibility loci. Objectives: Our genome-wide association study (GWAS) aimed to identify additional risk loci of genome-wide significance (GWS; p<5E-08) in European-derived primary SS. Methods: A total of 3232 cases and 17481 controls genotyped on GWAS arrays and 619 cases and 6171 controls genotyped on ImmunoChip (IC) arrays were imputed after quality control. Logistic regression was calculated adjusting for ancestry using the first 4 principal components to identify SS-associated SNPs. GWAS and IC results were meta-analyzed using weighted Z-scores. Bayesian statistics were used to assign posterior probabilities and define credible SNP sets for each locus. Bioinformatic analyses were used to predict functionality. Results: Seven novel loci exceeded GWS in the GWAS analysis: NAB1, MIR146A-PTTG1, XKR6, MAPT-CRHR1, RPTOR-CHMP6-BAIAP2, TYK2 and SYNGR1 . Meta-analysis with IC data identified three more novel loci exceeding GWS: CD247, PRDM1-ATG5 and TNFAIP3 . Several additional loci with suggestive association (p<1E-05) were also identified: ADAMTSL2, CGNL1 and PHRF1 . Several identified loci have reported functional implications in immune regulation and autoimmune disease. In lupus, rs2431697 correlated with rs2431098, which was shown to alter MIR146A expression, resulting in type I interferon pathway imbalance. Similarly, TYK2 risk association reportedly drives interferon, IL10 and RET signaling pathways. PRDM1 encodes Blimp-1, a master regulator of immune cell differentiation. CD247 encodes the zeta subunit of the T cell receptor complex. XKR6 is implicated in apoptotic cell ingestion. ATG5 is also involved in apoptosis, as well as autophagy and antigen presentation. Additional bioinformatics analyses (Haploreg, Regulome DB, ENCODE, etc.) revealed immune-relevant functional implications for each risk locus. The SS-associated credible set included variants downstream of TNFAIP3 in a region reported to abolish looping between an enhancer and the TNFAIP3 promoter in lupus and a coding variant that has been shown to alter NF-kB activity and neutrophil extra-cellular traps. The rs2293765 in the 5' UTR of NAB1 showed evidence of enhancer/promoter activities. The rs2069235 in the SYNGR1 locus showed enhancer and transcription start site activities in B and T cells. The rs7210219 in the MAPT-CRHR1 locus showed enhancer/promotor activities in various tissues. Conclusion: We have identified ten novel genetic susceptibility loci associated with SS pathology. Our finding increases the current number of GWS regions in SS patients of European origin, from 10 to 20. Future work is needed to identify and characterize the functional variants in each region. Disclosure of Interests: Bhuwan Khatri: None declared, Tove Ragna Reksten: None declared, Kandice L Tessneer: None declared, Astrid Rasmussen Speakers bureau: Novartis, ThermoFischer, R Hal Scofield Grant/research support from: Pfizer, Simon J. Bowman Consultant of: Astrazeneca, Biogen, BMS, Celgene, Medimmune, MTPharma, Novartis, Ono, UCB, xtlbio, Glapagos, Speakers bureau: Novartis, Joel Guthridge Grant/research support from: Xencor, Bristol Myers Squibb, DXterity, Judith A. James Grant/research support from: Progentec Diagnostics, Inc, Consultant of: Abbvie, Novartis, Jannsen, Lars Ronnblom Grant/research support from: AZ, Speakers bureau: AZ, Blake M Warner: None declared, Xavier Mariette: None declared, Roald Omdal: None declared, Javier Martin Ibanez: None declared, Maria Teruel: None declared, Janicke Liaaen Jensen: None declared, Lara A Aqrawi: None declared, Øyvind Palm: None declared, Marie Wahren-Herlenius: None declared, Torsten Witte: None declared, Roland Jonsson: None declared, Maureen Rischmueller: None declared, A Darise Farris Speakers bureau: Biogen, Marta Alarcon-Riquelme: None declared, Wan-fai Ng: None declared, Kathy L Sivils: None declared, Gunnel Nordmark: None declared, Christopher Lessard: None declared